Perceptual defense and perceptual vigilance in emotions recognizing task in gelotophobia predisposition - Klimova, K.K.; Kravchenko, Yu.E. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2025)
Context and relevance. Gelotophobia as fear of being laughed at was initially conceptualized as a neurotic symptom that subsequently showed considerable variability in non-clinical samples. One of the main features related to gelotophobia is the tendency to interpret others' smiles as less joyful and more scornful or malicious than non-gelotophobes do. This misattribution of smiles may impair adequate social integration of these individuals. Objective. The aim of the present issue was to examine whether these difficulties are related to a decrease in the accuracy of emotion recognition or to the specificity of processing successfully recognized emotions under the influence of perceptual strategies (perceptual defense and perceptual vigilance). Hypothesis. Perceptual strategies prolong the processing of emotional expression recognition, and hindering their work leads to an increase in errors specific to the hindered perceptual strategy. The strategies change the priority of processing stimuli with the aim of most quickly identifying (perceptual vigilance) or systematically ignoring their unpleasant aspects (perceptual defense). Methods and materials. Subjects (N = 202) were asked to identify four emotions (happiness, fear, anger, sadness, presented in Ogama 5.0.1) by facial expression and by the situation of experience as quickly and accurately as possible. The effectiveness of following these instructions was compared in conditions when the facial expression of emotion corresponded to the situation of experience and did not correspond. Gelotophobes and non-gelotophobes were compared according to the Mann-Whitney and Wilcoxon criteria. Results. Gelotophobes take longer but identify more accurately the expression of just happiness when stimuli are consistent (the facial expression and experimental circumstances refer to the same emotion), demonstrating both perceptual vigilance and perceptual defense. Statistically common error is that gelotophobes confuse a smile with an expression of fear. Conclusions. When stimuli are inconsistent, gelotophobes make more errors, indicating perceptual defense that extends to the recognition of all four emotions, not just happiness. Ignoring unpleasant aspects functions as an avoidance mechanism, the basic fear response pattern that underlies gelotophobia. Контекст и актуальность. Гелотофобия (боязнь осмеяния) - психологическая особенность, выделенная в исследованиях клиники неврозов, но впоследствии обнаруживаемая как самостоятельное явление, затрудняющее социальное взаимодействие во многом из-за неверной интерпретации позитивной экспрессии. Цель. Проверить, связаны ли эти трудности со снижением способности к распознанию эмоций или со спецификой переработки успешно распознанных эмоций в связи с потребностью защититься от неприятных переживаний вследствие осмеяния. Гипотеза. Защитные перцептивные стратегии удлиняют переработку эмоциональной экспрессии, а препятствование их работе приведет к росту ошибок, специфических для затрудненной перцептивной стратегии. Стратегии изменяют приоритетность переработки стимулов с целью наиболее быстрого выявления (перцептивная бдительность) или систематического игнорирования их неприятных аспектов (перцептивная защита). Методы и материалы. Участникам исследования (N = 202) предлагалось как можно быстрее и точнее определить 4 эмоции (радость, страх, гнев, печаль, предъявление в Ogama 5.0.1) по лицевой экспрессии и по контексту (ситуации переживания). Сравнивалась эффективность выполнения этих инструкций в условиях, когда лицевая экспрессия эмоций соответствовала ситуации переживания и не соответствовала ей. По результату сравнивались участники хотя бы с минимальной гелотофобией (опросник GELOPH-15) и участники без гелотофобии по критериям Манна-Уитни и Вилкоксона. Результаты. Обладатели гелотофобии тратят больше времени, но более точны при распознании только позитивной экспрессии в условиях, когда информация об эмоциях полна и непротиворечива, за счет меньшего количества ошибок, свойственных обеим перцептивным стратегиям. Статистически частотная ошибка состоит в том, что обладатели гелотофобии путают улыбку и экспрессию страха. При усложнении задачи распознания эмоции (лицевая экспрессия не соответствует обстоятельствам) активнее стратегия перцептивного избегания, и она распространяется на распознание всех эмоций исследования, а не только радости, что соответствует паттерну, образующему смысловую основу реакции страха, образующей ядро гелотофобии. Вывод. Причиной более медленного распознания позитивной экспрессии служит не активность, а конкуренция перцептивных стратегий.